1999
DOI: 10.1139/v99-162
|View full text |Cite
|
Sign up to set email alerts
|

La radiolyse de l'eau et des solutions aqueuses : historique et actualité

Abstract: Experiments showing that water is decomposed by the action of high-energy radiations date back to the first days of the discovery of radioactivity, a century ago. On the occasion of this anniversary, we have attempted to give a comprehensive account of the radiation chemistry of water and its solutions since its origin, with special emphasis on the various physical and chemical stages that led to the present state of this science. To this aim, we describe the effect of different intervening factors on the mole… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
94
0
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(98 citation statements)
references
References 276 publications
1
94
0
3
Order By: Relevance
“…Low-LET radiation (gamma radiation, accelerated electrons, high-energy X-rays) deposits energy discretely along the path of the particles whereas high-LET radiation (heavy ions, alpha particles and neutrons) deposits it densely. Gamma radiation of 60 Co has thus a LET value of 0.2-0.3 keV µm −1 whereas the value is 140 keV µm −1 in the case of 5.3 MeV alpha particles ( 210 Po) [8]. The LET is one of the important parameters to account for the yields of products obtained in radiolysis.…”
Section: Water Radiolysis: a Brief Historical Surveymentioning
confidence: 99%
“…Low-LET radiation (gamma radiation, accelerated electrons, high-energy X-rays) deposits energy discretely along the path of the particles whereas high-LET radiation (heavy ions, alpha particles and neutrons) deposits it densely. Gamma radiation of 60 Co has thus a LET value of 0.2-0.3 keV µm −1 whereas the value is 140 keV µm −1 in the case of 5.3 MeV alpha particles ( 210 Po) [8]. The LET is one of the important parameters to account for the yields of products obtained in radiolysis.…”
Section: Water Radiolysis: a Brief Historical Surveymentioning
confidence: 99%
“…These reactions include the dissociation of excited water molecules formed by recombination of the nonhydrated electron with its parent cation H 2 O + (geminate recombination) and the dissociative attachment of subexcitation-energy electrons (those that have kinetic energies lower than the firstelectronic excitation threshold of the medium, i.e., ~7.3 eV in liquid water) to a water molecule (DEA) [19]. Most of the rest of the formation of H 2 is due to the following combination reactions between e − aq and H atoms during spur/track expansion (typically, on time scales from ~1 ps to 1 μs) [6][7][8]10]:…”
Section: Theorymentioning
confidence: 99%
“…These species can promote corrosion, cracking, and hydrogen pickup both in the core and in the associated piping components of the reactor [1][2][3][4][5]. Theoretical calculations and chemical models of the radiation chemistry of water in the reactor core require the radiolytic yields (defined as the number of species formed or destroyed per 100 eV of energy absorbed [6,7]) of the primary species for both fast neutrons and γ-radiation. The rate constants for all of the reactions involving these species are also required.…”
Section: Introduction *mentioning
confidence: 99%
“…From the viewpoint of pure aqueous radiation chemistry, low-LET tracks are made up initially of strings of widely spaced Magee-type "spurs" (clusters of reactive species) [22,23] that develop independently in time (without interference from the neighboring spurs). During the physical and physicochemical stages of radiation action in Platzman's classification [24] (i.e., up to ∼1 ps after the initial energy deposition), the radiolysis of water can be described by the following reactions [25][26][27][28]:…”
Section: Low-let Radiolysis Of Liquid Watermentioning
confidence: 99%
“…, and g(H 2 O 2 ) = 0.68 molecules per 100 eV (for conversion into SI units (mol/J), 1 molecule per 100 eV ≈ 0.10364 μmol/J) [10,[26][27][28]. When the temperature is increased, measurements made in different laboratories with many different scavenger systems or directly by using pulse radiolysis (data up to 350°C have recently been compiled and reviewed by Elliot and Bartels [10]) have shown that the g values of the free radicals e − aq , H…”
Section: Low-let Radiolysis Of Liquid Watermentioning
confidence: 99%